Sexual behaviour and perception of HIV/AIDS among students in Ebonyi State University Abakaliki, Southeast Nigeria - Oliobi, Wendy Chinwe; Ikeotuonye, Arinze Chidiebere; Nwafor, Johnbosco Ifunanya; Onyema, Malachy Chizoba; Uche-Nwidagu, Bridget Nkiruka; Okoye, Paschal Chijioke; Nweke, Assumpta Nnenna (International Journal Of Community Medicine And Public Health, 2019)
Background: The sexual behaviour and practice increases the chances of contracting sexually transmitted infections including HIV/AIDS. Knowledge and perception of HIV/AIDS may be a determinant to sexual behaviour of the young adults. There this study aims to evaluate the sexual behaviour and perception of HIV/AIDS among university undergraduates of the Ebonyi State University Abakaliki. Methods: This was a cross-sectional descriptive study conducted between 5th March 2016 and 30th March 2016 among 406 undergraduates. An anonymous, self-administered, pre-tested questionnaire was used to collect the data from the participants. Statistical analysis was done using Epi Info 7.2.1. Results: The modal age group for sex debut was 20-24 years while the mean age at coitache among the study group was 20.2±4.6 years. More than a half of the respondents 173 (56.7%) had only one sex partner while the remaining had two or more sexual partners. Condom use in the last sexual intercourse was low as just more than a third of the respondents used condoms in their last sexual intercourse. Almost all the student had heard of HIV/AIDS 403 (99.3%). The mass media was the commonest source of obtaining information with regards HIV/AIDS among the study population. Males are more likely to have had sex compared to the female sex. Student who take alcohol regularly and those that take tobacco in any form were also more likely to have had sex compared to those who do not take alcohol or tobacco, (p value <0.0001). Conclusions: Sex is a common practice among the study population. Majority engage in risky sexual practices. There is an urgent need to improve the campaign on safer sex using the mass media as a veritable medium.